PERSEBARAN BANGUNAN PERTAHANAN JEPANG DI TELUKBETUNG KOTA BANDAR LAMPUNG - Iwan Hermawan (Balai Arkeologi Sumatera Utara, 2017)
Lampung is one of the strategic areas in Sumatera, because it is the gateway to the southern part of the island. The strategic position encouraged the Japanese to build defense structures (bunkers) in Telukbetung. The building of the defense structures was an anticipation effort to the Second World War. The problem in this article is the distribution of Japanese defense structures in Telukbetung, particularly the relation between the distribution of the Japanese defense structures and the strategy in dealing with the Second World War. The method being used is descriptive, and data collecting was carried out through bibliographical studies, survey, and interviews. Data analysis was done using the spatial approach. Based on their distribution, it seems like the defense structures in Telukbetung were built by taking into account the strategic locations and military strategy in anticipation to the Second World War.Lampung merupakan salah satu kawasan strategis di Sumatera, karena merupakan pintu gerbang pulau Sumatera di bagian selatan. posisi strategis tersebut mendorong Jepang untuk membangun bangunan pertahanan di Telukbetung. Pembangunan bangunan pertahanan tersebut dilakukan guna menghadapi Perang Dunia II. Permasalahan pada tulisan ini, adalah Persebaran Bangunan Pertahanan Jepang di Telukbetung, khususnya Hubungan antara persebaran bangunan pertahanan Jepang dengan strategi dalam menghadapi Perang Dunia II. Metode penelitian yang dipergunakan dalam penelitian ini adalah deskriptif, pengumpulan data dilakukan melalui studi pustaka, survey, dan wawancara. Analisis data dilakukan dengan menggunakan pendekatan keruangan. Berdasarkan persebarannya, bangunan pertahanan di Telukbetung dibangun dengan memperhatikan letak strategis dan strategi militer dalam menghadapi Perang Dunia II.